(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Bats are less vulnerable to forest fragmentation than any other mammal, and for that reason, some species can disperse to peri-urban or urban areas. Insectivore bats are abundant in urban areas due to the density of artificial roosts and insects attracted by city lights. Inter-species transmission of the rabies virus between bats can occur, and this is the most probable mechanism of virus circulation in bat populations. Bats can also transmit the rabies virus to other mammal species, like dogs and cats. With the halt of vaccination campaigns of dogs and cats in 2010, the importance of rabies surveillance in bats has increased in Brazil. In Campinas, Sao Paulo State, a passive surveillance system for bats was implemented in 1994 and rabies-positive bats from the families Molossidae, Phyllostomidae and Vespertilionidae were found in a peri-urban area. In these areas, a vaccination blockage in dogs and cats was recommended after the halt of the massive vaccination campaign in 2010. This control strategy was able to increase the proportion of vaccinated animals above a critical value while in the rest of the study area it did not. The probability of infectious contact between bats and dogs or cats was higher in the blockage areas, evidencing the importance of the implementation of control measures.